Experimental Study and Thermodynamic Modeling of Clonazepam Solubility in Supercritical Carbon Dioxide - Rojas-Sepulveda, A (Elsevier B.V., 2023)
In this work, the solubility of Clonazepam in supercritical carbon dioxide was tested at different temperatures (308 to 338 K) and pressures (12–30 MPa). The dissolved mole fractions of CLP in SC-CO2 ranged from 3.9×10−6 to 7.26×10−5. The experimental solubility of CLP was correlated using three methods: (1) Eight models that are based on density (Chrastil, K-J, Bartle et al., MST, Alwi–Garlapati, Del Valle–Aguilera, Adachi–Lu, and Sparks et al.); (2) equations of state (EoSs), more specifically the Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT), and the Soave–Redlich–Kwong equations of state (SRK); and (3) Association theory based models developed by Reddy-Madras, Rajasekhar-Madras model, Garlapati-Madras model, and a new modified association theory model. According to the findings, all examined models were able to produce acceptable fits with CLP solubility. The results showed the consistency of the models in correlating the solubility data across all the experimental conditions. To micro- or nanonize CLP, gas antisolvent processes could be the better option based on how CLP dissolves in SC-CO2. © 2023 Elsevier B.V.